Facial asymmetry and genetic ancestry in Latin American admixed populations - Quinto Sanchez, Mirsha (2015)
Fluctuating and directional asymmetry are aspects of morphological variation widely used to infer environmental and genetic factors affecting facial phenotypes. However, the genetic basis and environmental determinants of both asymmetry types is far from being completely known. The analysis of facial asymmetries in admixed individuais can be of help to characterize the impact of a genome's heterozygosity on the deveiopmental basis of both fl.uctuating and directional asymmetries. Here we characterize the association between genetic ancestry and individual asymmetry on a sample of Latin-American admixed populations. To do so, three-dimensional (3D) facial shape attributes were explored on a sample of 4,104 volunteers aged between 18 and 85 years. Individual ancestry and heterozygosity was estimated using more than 730,000 genome-wide markers. Multivariate techniques applied to geometric morphometric data were used to evaluate the magnitude and significance of directional and ftuctuating asymmetry (FA), as well as correiations and multipie regressions aimed to estimate the relationship between facial FA scores and heterozygosity and a set of covariates. Resuits indicate that directional and FA are both signi:ficant, the former being the strongest expression of asymmetry in this sample. In addition, our analyses suggest that there are some specific patterns of facial asymmetries characterizing the different ancestry groups. Finally, we find that more heterozygous individuais exhibit lower leveis of asymmetry. Our results highlight the importance of including ancestry-admixture estimators, especially when the analyses are aimed to compare leveis of asymmetries on groups differing on socioeconomic leveis, as a proxy to estimate developmental noise.